Draft Fourth Five Year Plan (1966-71) Part -1 - Planning Commission (Planning Commission, 1966)
The Union Territory of Pondicherry comprises the four regions of Pondicherry, Karaikal, Mahe and Yanam, covering an area of about 479.2 sq. kms, with a population of 3.69 lakhs, according to the 1961 Census. The First Five Year Plan which was ushered in 1951 did not cover Pondicherry, as it was transferred to Indian Union on de facto basis, only in November 1954. At the time of transfer the administrative machinery available was of the most rudimentary type.
Union Territory of Pondicherry